TRAINING DEVELOPMENTAS A KEY FACTOR IN HUMAN CAPITAL IN THE KNOWLEDGE-BASEDECONOMY (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article made the issue of staff training as part of perfecting the quality of human capital and their impact on efficiency. It was assumed that by participating in training, improves the work efficiency of employees
Keywords: human capital, training, efficiency, work, KE